Raising Cybersecurity Awareness among College Students (Journal of The Colloquium for Information Systems Security Education, 2016)
Cybersecurity is of increasing importance due to the rise in reliance on digital equipment and programs to manage our daily lives, including the transmission and storage of personal information. Research studies establish that an effective security awareness program is one of the most important steps towards increasing cybersecurity. In this project we set out to understand the current level of security awareness among college students and develop a module that will help raise their awareness. The main features of our module are interactivity and the presentation of shocking consequences of careless cyber habits of common Internet/technology users. We designed a survey that includes pre and post-tests to fulfill the goals of our project and administered it to students on our campus. Our survey results indicate that the module has been effective particularly among non-Computer Science majors. It has raised their level of awareness not only for the specific topics that the module addresses but overall in cybersecurity.